Are killer bees good for coffee? The contribution of a paper's title and other factors to its future citations. (January 2019) - Costello, Mark J.; Beard, Karen H.; Primack, Richard B.; Devictor, Vincent; Bates, Amanda E.
Abstract: How can the title of a paper affect its subsequent number of citations? We compared the citation rate of 5941 papers published in the journal Biological Conservation from 1968 to 2012 in relation to: paper length; title length; number of authors; paper age; presence of punctuation (colons, commas or question marks); geographic and taxonomic breadth; the word 'method'; and the type of manuscript (article, review). The total number of citations increased in more recently published papers and thus we corrected citation rate (average number of citations per year since publication) by publication age. As expected, review papers had, on average, twice the number of citations compared to other types of articles. Papers with the greatest geographic or taxonomic breadth were cited up to twice as frequently as narrowly focused papers. Titles phrased as questions, shorter titles, and papers with more authors had slightly higher numbers of citations. However, overall, we found that the included parameters explained only 12% of the variability in citation rate. This suggests that finding a good title is necessary, but that other factors are more important to construct a well-cited paper. We suggest that to become highly cited, a primary requirement is that papers need to advance the science significantly and be useful to readers.